Synthesis and electrochemical studies of iron oxide-based hybrids for lithium ion batteries - Hao, Shiji (2018)
With increasing demand for enhanced lithium ion batteries applied in electronic vehicles, hybrid vehicles and mobile electronics, intensive research is being focused on exploring new generation anode materials with high storage capacity, low cost and great safety. Transition metal oxides, as a kind of promising candidates, have attracted much attention and shown much higher capacities, compared with carbon based anode materials (372 mAh g-1), through conversion or insertion/extraction reaction. Among them, iron oxide is of great interest due to its high corrosion resistance, abundance, nontoxicity and low cost. However, there still exist several issues (e.g. low electronic conductivity and large volume change) needed to be addressed before the large-scale commercialization of iron oxide based anodes. Therefore, it’s necessary to conduct scientific studies to further investigate and improve their electrochemical performance and behavior as anodes for lithium ion batteries. Design of novel hybrid nanostructure has been proved to be an effective approach to the technical bottleneck of electrode materials. The hybrid materials present desirable properties by integrating various functions into a single system. In view of the iron oxide/carbon hybrids, Fe3O4@porous carbon matrix and Fe3O4@porous carbon matrix/graphene, are synthesized and the nanostructure’s effect on their electrochemical performance is investigated in depth in this thesis. In the well-defined iron oxide/carbon hybrids, the conductivity and electrical contact of nanocomposites are improved with additive carbon materials. Moreover, hierarchical porous framework can offer large electrode/electrolyte contact area and shorten diffusion distance of lithium ions, which is crucial for the good rate capability. Meanwhile, the cushion to volume change can be provided from the reserved void and porosity during the charge/discharge process. However, the hybridization between metal oxide and carbon species still exhibits a limited improvement, due to the restricted theoretical capacity of carbon species. The mixture of metal oxides with well-fined micro/nanostructures can endow composites with much improved capacity and remarkable rate capability. Therefore, a series of Fe2O3/MnO2 nanocomposites are prepared via controllable annealing conditions. As demonstrated in characterization and performance evaluation, the hollow-structured oxygen-vacancy-rich Fe2O3/MnO2 provides superior electrochemical properites as anode materials for lithium ion batteries, ascribing to their increased contact area with electrolyte and enhanced electronic and ionic conductivity. To further reveal the structure and morphology evolution of iron oxide based anodes during long-term electrochemical cycling, the investigation of hollow-porous Fe2O3 microspheres is conducted via ex-situ X-ray diffraction (XRD) and ex-situ transmission electron microscopy (TEM) techniques. As revealed in the test results, a crystal size induced phase transition (α → γ → β) is found to be contributed to an abnormal performance fluctuation during cycling. These research results are expected to make insightful suggestions to other scientific studies.